ALTERNATIVE SOLUTION &EVALUATION OF TRUNKLINE SYSTEM AS THE SOLUTION OF THE BOTTLENECK PROBLEM IN OIL PIPELINE NETWORK (Case Study Field X onshore Southern Sumatera Region) - FITHRA MS (NIM : 222 10 083), ZEKI
Field X has been producing oil for more than 15 years. Now this field has its production rate in about 1128.51 BLPD and water-cut 45%. This field has a bad piping system that it causes the liquid which in the storage tank in each source could not be transferred to the main gathering station all at the same times. The solution to this problem is by doing a modification to the pipeline system in order to increase the deliverable rate of liquid to the main GS. The problem which is usually happened is what we called bottleneck. Bottleneck is a condition where a small diameter of pipe is causing a high pressure drop in pipe. This drop is causing the flowrate of liquid could not be maximally transported to the gathering station and making the pumps which are in each source have to operate one at a time. This paper explains the engineering solution which is applied in the surface facility in order to increase the deliverable rate from the source through the trunkline system to the final storage in the main gathering station. In order to modeling that, we made a series of pipeline model which is nearly similar to the real field condition. The result from this simulation then is analyzed at which point give a pressure drop higher than usual. Then we start to modificate by using branch pipe in place which there is a high pressure drop inspected. Other modification is by using paralel pipe in line with the main pipeline in existing condition. By the end of the simulation, we chose the best solution that can be done and the most applicable in this field based on the technical analysis and economical factor.